Reminder of the Validity Period of the Diagnostic and or Interventional Radiology Permit for Computed Tomography Scans (Ct Scans) for Advanced Referral Health Facilities of BPJS Health Jember Branch’s Partners - M. Suhron; Widya Waskito (Universitas STRADA Indonesia, 2025)
Background: BPJS Health requires Health Facilities to fill in health service profiles in the form of human resources, facilities, and infrastructure owned into the BPJS Health Facilities information system (HFIS). Purpose: Expalanation Reminder Feature for the validity period of the Diagnostic and/or Interventional Radiology Permit for Computed Tomography Scan (CT Scan) which is directly sent to the hospital's correspondence email is still not accommodated. Methods: The method used in this innovation is Action Research, with a research population of 14 Advanced Referral Health Facilities partners of BPJS Health Jember Branch and a research sample of 3 Advanced Referral Health partners of BPJS Health Jember Branch. Results: Respondents in the 26-35 years age group were 66.7% and the 36-45 years age range was 33.3%. 3 Hospitals filled out the survey, namely Citra Husada Jember Hospital (33.3%), Siloam Jember Hospital (33.3%), and Balung Hospital (33.3%). Category scores using the Mean Hypotetic and Results Validation of responses to innovations from service quality, showing 100% of respondents gave a good response of Siloam Jember Hospital. Conclusion: This means that the quality of this reminder innovation from the service quality dimension is well received. The innovation of a Reminder of the Validity Period of Diagnostic Radiology Permit and/or Interventional Computed Tomography Scan (CT Scan) for Advanced Referral Health Facilities of BPJS Health Jember Branch partner can be recommended for implementation.